Whey cheeses (heat coagulated) - Papademas, Photis; Bintsis, Thomas; Alichanidis, Efstathios S.; Ardö, Ylva (My University, 2017)
This chapter discusses various types of whey cheeses such as, Anari cheese, Anthotyros cheese and Manouri Protected Designation of Origin (PDO) cheese. Anari is a whey cheese produced during the manufacture of Halloumi cheese. Fresh Anari is a soft, high-moisture, fragile cheese, with a very mild nutty sweet flavour, and it can be sold in vacuum packs either slightly salted or not. Anari cheese is usually dried, under cold air streams, in specially designed drying rooms until it becomes hard and easy to grate. Anthotyros cheese has a compact, closed body and a typical mild pleasant flavour. Manouri is a whey cheese which is manufactured in Thessaly, Western and Central Macedonia. Manouri cheese has a compact, closed body and a rich flavour with creamy, fatty notes. Mesost and Messmör are unripened whey cheeses that differ from each other only in water content. Mesost and Messmör contain milk sugar, lactose, whey proteins and sometimes milk fat.
Keywords: Anari cheese; Anthotyros cheese; Healthy milk minerals; Lactose; Manouri PDO cheese; Mesost and Messmör cheese; Milk fat; Whey proteins